Responsible Design, Implementation and Use of Information and Communication Technology: 19th IFIP WG 6.11 Conference on e-Business, e-Services, and e-Society, I3E 2020, Skukuza, South Africa, April 6–8, 2020, Proceedings, Part I - Hattingh, Marié; Matthee, Machdel; Smuts, Hanlie; Pappas, Ilias; Dwivedi, Yogesh K.; Mäntymäki, Matti (Lecture Notes in Computer Science, 2020)
Book Front Matter of LNCS 12066